Maternal serum protein profile and immune response protein subunits as markers for non‐invasive prenatal diagnosis of trisomy 21, 18, and 13. (1st February 2013) - Narasimhan, Kothandaraman; Lin, Su Lin; Tong, Terry; Baig, Sonia; Ho, Sherry; Sukumar, Ponnusamy; Biswas, Arijit; Hahn, Sinuhe; Bajic, Vladimir B.; Choolani, Mahesh
ABSTRACT Objectives To use proteomics to identify and characterize proteins in maternal serum from patients at high‐risk for fetal trisomy 21, trisomy 18, and trisomy 13 on the basis of ultrasound and maternal serum triple tests. Methods We performed a comprehensive proteomic analysis on 23 trisomy cases and 85 normal cases during the early second trimester of pregnancy. Protein profiling along with conventional sodium dodecyl sulfate polyacrylamide gel electrophoresis/Tandem mass spectrometry analysis was carried out to characterize proteins associated with each trisomy condition and later validated using Western blot. Results Protein profiling approach using surface enhanced laser desorption/ionization time‐of‐flight mass (SELDI‐TOF/MS) spectrometry resulted in the identification of 37 unique hydrophobic proteomic features for three trisomy conditions. Using sodium dodecyl sulfate polyacrylamide gel electrophoresis followed by Matrix Assisted Laser Desorption Ionization – Time of Flight/Time of Flight (MALDI‐TOF/TOF) and western blot, glyco proteins such as alpha‐1‐antitrypsin, apolipoprotein E, apolipoprotein H, and serum carrier protein transthyretin were identified as potential maternal serum markers for fetal trisomy condition. The identified proteins showed differential expression at the subunit level. . Conclusions Maternal serum protein profiling using proteomics may allow non‐invasive diagnostic testing for the most common trisomies and may complement ultrasound‐based methods to more accurately determine pregnancies with fetal aneuploidies. © 2013 John Wiley & Sons, Ltd.